Cell Culture - Ali Mehanna, Radwa (IntechOpen, 2019)
Cell culture is one of the major tools used in cellular and molecular biology, delivering an excellent model for studying the normal physiology and biochemistry of cells. This book covers some advanced aspects in cell culture methodologies. The book has four sections discussing different types of cell culture models, including 3D cell culture techniques, their advantages, and limitations in comparison to traditional 2D culturing; cell viability, autophagy, in vitro toxicity tests and live cell imaging; stem cell culture for cell-based therapeutics; and specific applications and methodologies for hybrid cell lines and cancer models. This book provides a comprehensive overview of some of the advanced cell culture methodologies and applications. It serves as a valuable source for scientists, researchers, clinicians and students.